Informal tourism entrepreneurs' capital usage and conversion. Issue 18 (8th November 2019) - Çakmak, Erdinç; Lie, Rico; Selwyn, Tom
ABSTRACT: This article examines informal entrepreneurs' capital usage and conversion in the Thai tourism sector. On the Bourdieusian assumption that people perpetually transform tangible and intangible forms of capital, this study seeks to answer how informal tourism entrepreneurs transform intangible capital into tangible capital, and vice versa, at different stages of their development process. A visual dataset of 78 filmed interviews and of 426 photographs of informal entrepreneurs in three tourist-island destinations in Thailand was compiled and analysed using thematic qualitative analysis. The results show the importance of diversification of capital mix at informal entrepreneurs' different development stages. Whereas cultural and symbolic capital are more salient for freelancers and small-size entrepreneurs, economic and social capital are more important for mid-size and large informal entrepreneurs. Furthermore, this study introduces dream capital as a new form of capital. Developing countries are recommended to introduce a policy on profiling informal tourism entrepreneurs so that the appropriate level of regulation can be applied in order to maintain or increase their benefits to society.